Type of Participation of Rural Working and Non - Working women In Home Activities - Rathod, Shital; Solunke, Jyoti (IJRDO - Journal of Applied Management Science, 2017)
Homemaking is considered as one of the World’s major occupations involving a core of household activities essential for our existence, like any other profession homemaking is also a profession. The present research study is planned with objectives to find out the Personal characteristics of rural working and non working women, to know the type of participation of rural working and non working women, Assessment of Home activities of selected rural working and non working women will be investigated. Seventy five (75) women from rural areas of Takli (Kumbhkarn) district Parbhani will be covered for the present study. This study will be investigated in one phases that was type of participation of the rural working and non working women investigated. Results indicated that independent participation of the women was found in Chapati/ bhakri making, serving food, Washing cloth, Mopping floor and House decoration. Joint participation with female was observed in Cleaning & cutting vegetables and Actual preparation of curry while joint participation with male was noticed in ornaments purchasing and Cloth purchasing. Where as no participation of respondents were observed in Utensil purchasing, Medicine purchasing, getting them ready for school, sending to tuition.